Kekuatan Akta Jual Beli Tanah Di Pengadilan Agama (Studi Kasus Pengadilan Agama Mataram) - Rina Khairani Pancaningrum; Ridwan Ridwan; Fatahullah Fatahullah (Journal Kompilasi Hukum, 2019)
This research examines the strength of land sale and purchase certificates in religious courts and the factors that influence them. The research objective is to find out, explain, analyze and obtain answers about the strength of the land sale and purchase deeds at the Religious Courts and the factors that influence them. This study uses normative/doctrinal legal research methods to find law in concreto cases in the form of determining the legal force of proof of land sale and purchase deeds at the Religious Courts and the factors that influence them. Based on the results of the study, it can be concluded that first, the strength of the land sale and purchase deed in the Religious Court has perfect and binding strength if the deed is not denied by the opposing party, denied by the opposing party but strengthened by other evidence or photocopy that has been nazegelen (sufficiently stamped), matched with the original which turned out to be appropriate, then the Chairperson of the Assembly was given the code, date and initial of the Chairperson of the Assembly and other evidence was strengthened, and secondly, the factors that influenced the strength of the land sale and purchase deeds at the Religious Court were the fulfillment of formal and material requirements for the deed of sale and purchase, so that the evidence has perfect and binding strength, in accordance with Article 1875 of the Civil Code / BW and the absence of denial by the opposing party on the deed submitted as evidence, the existence of land denial as ownership rights is caused by because of ignorance of one of the parties who litigated well because it did not pe have not bought the land in question, do not know of its existence or the land has been transferred, and the existence of other evidence and local examination by the Panel of Judges (descente) that supports the truth of the deed.